OFFICE ROLES, FUNCTIONS AND OBJECTIVES - Rindani, Adia; Afrilisna, Venny; Harahap, Nasrun (International Journal of Multidisciplinary Reseach, 2025)
In general, an office can be defined as a place or space used to carry out business activities or administrative tasks. More specifically, an office refers to a building, house, or room that functions as a work management center. This article aims to examine the role, function, and purpose of office activities. This study uses a literature study approach, with data sources obtained from the results of searching for references to books and scientific journals that discuss related topics. Office administration has a strategic position in supporting the achievement of organizational goals. Through its various functions, such as receiving, recording, managing, and conveying information and maintaining assets, office administration is an important element in ensuring the smooth operation of an organization. Optimal office management is required to be able to plan, organize, direct, and supervise office activities in a structured manner. The main purpose of office management is to provide accurate, efficient, and accountable information services and recording systems, in order to support the decision-making process, operational continuity, and service to partners and customers.